A thermally engineered polydopamine and bacterial nanocellulose bilayer membrane for photothermal membrane distillation with bactericidal capability. (January 2021) - Wu, Xuanhao; Cao, Sisi; Ghim, Deoukchen; Jiang, Qisheng; Singamaneni, Srikanth; Jun, Young-Shin
Abstract: Solar energy holds great promise for sustainable desalination to alleviate global water scarcity. Recently developed solar steam generation relying on interfacial evaporators has high solar energy-to-steam efficiency (60–90%), but its vapor collection efficiency is low, typically ~30%. Here, we present a solar-driven photothermal membrane distillation (PMD) system that offers easy and highly efficient clean vapor generation, condensation, and collection. The new photothermal membrane is thermally-engineered to incorporate a bilayer structure composed of two environmentally-sustainable materials, polydopamine (PDA) particles and bacterial nanocellulose (BNC), and it achieved a permeate flux of 1.0 kg m −2  h −1 under 1 sun irradiation and a high solar energy-to-collected water efficiency of 68%. The thermally-engineered strategy of using a bilayer structure ensures superb optical/photothermal activities, maximized membrane porosity (~93%), and reduced conductive heat transfer, thus increasing the thermal efficiency of the membrane. The strong chemically-bonded fluorosilane functional groups on the membrane surface provide stable hydrophobicity and high salt rejection (>99.9%). Moreover, under solar irradiation, the membrane shows effective interfacial photothermal disinfection to kill bacteria, enabling easy cleaning and increasing its lifespan. Using solar energy, the PMD system presented here can provide advantageous decentralized desalination for remote areas, and can support resilient community development. Graphical abstract: Image 1